A comparative analysis of the influence of human salivary enzymes on odorant concentration in three palm wines. - Olusegun, Lasekan (MDPI, 2013)
The influence of human salivary enzymes on palm wines’ odorant concentrations were investigated by the application of aroma extracts dilution analysis (AEDA) and by the calculation of odour activity values (OAVs), respectively. The odorants were quantified by means of stable isotope dilution assays (SIDA), and the degradation profiles of odorants by human saliva were also studied. Results revealed 46 odour-active compounds in the flavour dilution (FD) factor range of 4-256, and all were subsequently identified. Of the 46 odorants, 41 were identified in the Elaeis guineensis wine, 36 in Raphia hookeri wine and 29 in Borassus flabellifer wine. Among the odorants, the highest FD-factors were obtained from acetoin, 2-acetyl-1-pyrroline and 3-isobutyl-2-methoxypyrazine. Among the 13 potent odorants identified, five aroma compounds are reported here as important contributors to palm wine aroma, namely 3-isobutyl-2-methoxy-pyrazine, acetoin, 2-acetyl-1-pyrroline, 3-methylbutylacetate and ethyl hexanoate. Meanwhile, salivary enzymic degradation of odorants was more pronounced among the aldehydes, esters and thiols.